2012
DOI: 10.1016/j.schres.2012.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Impact on intracortical myelination trajectory of long acting injection versus oral risperidone in first-episode schizophrenia

Abstract: Context Imaging and post-mortem studies suggest that frontal lobe intracortical myelination is dysregulated in schizophrenia (SZ). Prior MRI studies suggested that early in treatment of SZ, antipsychotic medications initially increase frontal lobe intracortical myelin (ICM) volume, which subsequently declines prematurely in chronic stages of the disease. Insofar as the trajectory of ICM decline in chronic SZ is due to medication non-adherence or pharmacokinetics, it may be modifiable by long acting injection (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 73 publications
2
59
0
1
Order By: Relevance
“…The superiority of long-acting injectable risperidone extends beyond preventing psychotic symptom return. Use of long-acting injectable risperidone in our first-episode patients also led to better maintenance of intracortical myelination 22 as well as improved cognitive functioning. 23 If this trifecta of improved psychotic symptom control, cognition, and intracortical myelination can be replicated in longer longitudinal studies of patients with a first episode of schizophrenia, it would suggest that the use of long-acting injectable antipsychotics early in schizophrenia can modify the trajectory of the disorder and lead to better long-term outcomes.…”
Section: Discussionmentioning
confidence: 70%
“…The superiority of long-acting injectable risperidone extends beyond preventing psychotic symptom return. Use of long-acting injectable risperidone in our first-episode patients also led to better maintenance of intracortical myelination 22 as well as improved cognitive functioning. 23 If this trifecta of improved psychotic symptom control, cognition, and intracortical myelination can be replicated in longer longitudinal studies of patients with a first episode of schizophrenia, it would suggest that the use of long-acting injectable antipsychotics early in schizophrenia can modify the trajectory of the disorder and lead to better long-term outcomes.…”
Section: Discussionmentioning
confidence: 70%
“…Interesting, mortality was highest in those who were not medicated [138]. Moreover, several MRI studies [139,140] suggest that early in the treatment of schizophrenia, antipsychotic medications, and more specifically some long-acting SGAs, promote frontal lobe white matter volume, and specifically myelination of the lower layers of the cortex. This is important as dysregulation of the normal myelination trajectory may contribute to the functional deterioration and treatment resistance observed in chronic schizophrenia [139].…”
Section: Results Of Descriptivementioning
confidence: 99%
“…However, a study carried out in recently diagnosed patients showed that prolonged treatment with the SGA RLAI was associated with stable white matter volume in comparison with a decrease in volume observed in patients treated with the oral formulation of the same molecule [Bartzokis et al 2012]. These data suggest that, by modifying adherence, RLAI may differentially impact myelination and account for the better long-term outcomes compared with oral risperidone.…”
Section: The Importance Of Ensuring Treatment Continuity In Schizophrmentioning
confidence: 97%